Genome‐wide analysis of DNA methylation in relation to socioeconomic status during development and early adulthood. Issue 1 (16th February 2019) - McDade, Thomas W.; Ryan, Calen P.; Jones, Meaghan J.; Hoke, Morgan K.; Borja, Judith; Miller, Gregory E.; Kuzawa, Christopher W.; Kobor, Michael S.
Abstract: Objectives: Socioeconomic status (SES) is a powerful determinant of health, but the underlying biological mechanisms are poorly understood. This study investigates whether levels of DNA methylation at CpG sites across the genome are associated with SES in a cohort of young adults in the Philippines. Methods: DNA methylation was assayed with the Illumina HumanMethylation450 Bead Chip, in leukocytes from 489 participants in the Cebu Longitudinal Health and Nutrition Survey (mean age = 20.9 years). SES was measured in infancy/childhood and adulthood, and was based on composite measures of income, assets, and education. Genome‐wide analysis of variable probes identified CpG sites significantly associated with SES after adjustment for multiple comparisons. Functional enrichment analysis was used to identify biological pathways associated with these sites. Results: A total of 2, 546 CpG sites, across 1, 537 annotated genes, were differentially methylated in association with SES. In comparison with high SES, low SES was associated with increased methylation at 1, 777 sites, and decreased methylation at 769 sites. Functional enrichment analysis identified over‐representation of biological pathways related to immune function, skeletal development, and development of the nervous system. Conclusions: Socioeconomic status predicts DNA methylation at a large number of CpG sites across the genome. The scope of these associations is commensurate with the wide range of biological systems and health outcomes that are shaped by SES, and these findings suggest that DNA methylation may play an important role.